Community Empowerment of the Low Income Muslims in Cirebon City Through Participatory Action Research (Journal of Namibian Studies : History Politics Culture, 2023)
The study aims to empower low-income people through participatory action research in the city of Cirebon. The research method used is participatory action research. Resources come from primary and secondary data in the form of public documents from the Office of Social Manpower and Transmigration; Strategic Plan Document (RENSTRA) of the Education Office of Indramayu Regency for 2016-2021; and relevant literature. The results of the study consist of two sub-discussions. First, based on the results of the analysis using CIPPO, it was found that all APR activities carried out by the Government, local governments, universities, NGOs, and companies were all successful, and had a positive impact both directly and indirectly on increasing people's income. second, the PAR program is able to increase the adjustment between very priority needs and the programs provided to the community. This conformity can be realized because before carrying out the empowerment program, NA is carried out directly from the community. The process of planning, implementing, evaluating, and utilizing the results of programs provided to the community must involve local communities. When the community is involved from planning, implementing, evaluating, and using the program, the feelings felt by the community will increase. When the sense of ownership is high, the maintenance program for existing assets becomes lighter, has a longer lifespan and provides more welfare to the community. From the perspective of Islamic Economics, the people of the Balongan Indramayu area of West Java are said to have fulfilled basic physical needs such as food and shelter, but also non-physical such as education and spirituality. The fulfillment of primary needs (Dlaruriyyat), secondary needs (Hajiyyat) and tertiary needs (Tahsiniyyat). It's just that the implementation of the program has not been maximized, therefore it needs to be maximized in order to improve the welfare of the community as a whole.